Cerebral and Cerebellar Cortex Interaction and Dynamics in Health and Disease - Baloyannis, Stavros J. (IntechOpen, 2021)
Cerebral and Cerebellar Cortex - Interaction and Dynamics in Health and Disease discusses several important issues of cerebro-cerebellar collaboration and interactions. The morphological and functional study of the cerebral and cerebellar cortices and their interaction has considerable value for interpreting the clinical phenomenology of cortical degenerations in the initial stage of the disease. In addition, the analysis of cerebro-cerebellar interactions strongly supports the concept of the close functional unity and harmonization of the brain and the cerebellum, underlining the important role that the cerebellar cortex plays in the performance of higher mental faculties, creativity, emotional processes, and homeostatic equilibrium of the human body.